-27=3(4x+3)

Simple and best practice solution for -27=3(4x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=3(4x+3) equation:


Simplifying
-27 = 3(4x + 3)

Reorder the terms:
-27 = 3(3 + 4x)
-27 = (3 * 3 + 4x * 3)
-27 = (9 + 12x)

Solving
-27 = 9 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-27 + -12x = 9 + 12x + -12x

Combine like terms: 12x + -12x = 0
-27 + -12x = 9 + 0
-27 + -12x = 9

Add '27' to each side of the equation.
-27 + 27 + -12x = 9 + 27

Combine like terms: -27 + 27 = 0
0 + -12x = 9 + 27
-12x = 9 + 27

Combine like terms: 9 + 27 = 36
-12x = 36

Divide each side by '-12'.
x = -3

Simplifying
x = -3

See similar equations:

| 35x+3x-9=180 | | (-8+5m)(5)= | | 42x/70x= | | -m^2-9m=-5m+10 | | 7.1x-1.2=20.1 | | -10-3b=b+6 | | 4x+6x=132 | | 30/r=5 | | 5x-4(2x-7)=13 | | 6(4z-1)-3(z+9)=14(z+1) | | 3x+(x+18)=90 | | -6k+7k+5=-5+3k | | -4(t-4)-(t+3)=8 | | 2x+(x+78)=180 | | 7+6(x-2)=9-2(x-9) | | -3.33=.50x | | x+3(-x-6)=-18 | | 12x^2-360x+2025=0 | | -3.33=-.50 | | 3=lnx+ln(x+2) | | (5c+3)(3c-5)= | | ly+3l=17 | | -6-7v=-6(4v+1) | | 8x+133=15x | | -4b-40=2(-4b-8)+4 | | C=2.75p+3.00 | | 4/7=n/18 | | -27-3n=-6(3+n) | | 3(x+2)-1=3x+6 | | 2+16y=3x+42 | | 8+3w=14 | | 3-4(4x+2)=35-8x |

Equations solver categories